2003
DOI: 10.1038/sj.ejcn.1601707
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of plasma homocysteine and serum methylmalonate concentrations in apparently healthy elderly subjects after treatment with folic acid, vitamin B12 and vitamin B6: a randomised trial

Abstract: Objectives: To investigate, in an elderly population: (1) the effects of oral B-vitamin therapy on P-tHcys, S-MMA and Hb/MCV, (2) the appropriate decision limit for 'high' metabolite concentrations and (3) the estimated prevalence of vitamin B 12 /folate deficiency on the basis of different decision limits. Design: Double-blind placebo-controlled intervention study. Setting: Outpatient clinic. Subjects: A total of 209 community-dwelling subjects, median age 76 y (range 70-93) y. Intervention: Four months of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 59 publications
2
28
1
1
Order By: Relevance
“…However, in the elderly, vitamin replete men have higher tHcy values than women, 33 pointing to the necessity of adequate vitamin measurements for the diagnosis of deficiency in the old age groups. Although our study, from a strict epidemiologic perspective might have some selection bias, we believe that the results are applicable to the elderly population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the elderly, vitamin replete men have higher tHcy values than women, 33 pointing to the necessity of adequate vitamin measurements for the diagnosis of deficiency in the old age groups. Although our study, from a strict epidemiologic perspective might have some selection bias, we believe that the results are applicable to the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…17 For holoTC, we found a lower reference limit of 19.6 pmol/L, which is in accordance with the manufacturer's recommendations and some 13,25 but not other 32 studies, probably due to different populations studied. When calculating reference intervals we used exclusion criteria for the healthy subgroup partly based on our previous data, 33 and we used very strict criteria when excluding unhealthy individuals. For holoTC and total cobalamin, the lower reference limits did not markedly change after exclusion of 'non-healthy' subjects and they were in the same range as laboratory standards.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a signifi cant infl uence of cobalamin intake on serum concentrations in our study population may be due to the low variability of cobalamin intake and/or the alleged higher alimentary intake in the SV subgroup, which ingested cobalamin in form of enriched foods. Intervention studies show that an additional cobalamin intake can suffi ciently increase low serum concentrations and decrease elevated homocysteine concentrations [44] . Multiple linear regression analysis showed that cobalamin status and duration of adhering to the vegan diet were predictive for the homocysteine concentrations in our collective.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there is an inverse relationship between plasma B vitamin concentrations that are involved in the metabolism of homocysteine, especially folate, and plasma total homocysteine (tHcy) concentrations (8)(9)(10). In 1996, the U.S. FDA required that all enriched grain products be fortified with folic acid by January, 1998, to increase folate intake among childbearing-aged women and thus reduce the risk of neural-tube defects in newborns.…”
Section: Introductionmentioning
confidence: 98%